2005
DOI: 10.1097/01.jom.0000161732.96555.2b
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Airway Effects of Seafood Industry Workers in Northern Norway

Abstract: Seafood industry workers showed a high prevalence of work-related airway symptoms. Further research on the relationship between exposure and effects is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 24 publications
8
52
0
Order By: Relevance
“…1,5 Asthma prevalence among trawler workers was 3.9% and is consistent with previously reported asthma prevalence of between 2 and 8% in workers processing bony fish, irrespective of industry type. 19 Work-related COPD has previously been described in occupational environments where bioaerosols are an important exposure.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…1,5 Asthma prevalence among trawler workers was 3.9% and is consistent with previously reported asthma prevalence of between 2 and 8% in workers processing bony fish, irrespective of industry type. 19 Work-related COPD has previously been described in occupational environments where bioaerosols are an important exposure.…”
Section: Discussionsupporting
confidence: 77%
“…1,24 The two-part self-administered questionnaire included questions on socio-demographic, health, and occupational characteristics. The first part contained questions on demographic data, smoking habits, and respiratory and allergic diseases.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhalation of particulate matter may affect the airway epithelial cells and previous studies have shown that production workers in the seafood industry inhale aerosols containing biological material (Bang et al, 2005;Jeebhay et al, 2005). Reports by Bang and co-workers (2005) and Shiryaeva and coworkers (2010) show an enhanced occurrence of respiratory symptoms from both the upper and lower parts of the airways in workers in the Norwegian salmon industry.…”
Section: Introductionmentioning
confidence: 99%
“…Workers processing seafood are exposed to bioaerosols in their breathing zone that may be inhaled (Bang et al 2005;Weytjens et al 1999;Shiryaeva et al 2013). Bioaerosols are particulate matter or liquid droplets suspended in air, containing agents of biological origin such as endotoxins, microorganisms, and proteins including high molecular weight allergens and enzymes Bang et al 2005) depending on the type of seafood being processed Jeebhay et al 2001).…”
Section: Introductionmentioning
confidence: 99%